liyaas1
contestada

Can you help me in this question?

(Also please write me how to solve it and ill check the answer if it is true then i will make you the brainliest.)

Can you help me in this question Also please write me how to solve it and ill check the answer if it is true then i will make you the brainliest class=

Respuesta :

Answer:

C

Step-by-step explanation:

2m + 3m = 5m

9m - 5m = 4m

11m - 6m = 5m

Therefore, the expression 11m - 6m is equivalent to 2m + 3m

(as they both equal 5m)

Answer:

C. The expression 11m - 6m is equivalent to 2m + 3m.

Step-by-step explanation:

9m - 5m = 4m

11m - 6m = 5m

2m + 3m = 5m